Effect of pancreatic kallikrein and trypsin inhibitors on the course of postischemic toxemia - Kharchenko, V Z; Protsenko, V A (Farmakologiia i toksikologiia, 1977)
By studying the ECG findings, dynamic changes of the body temperature, the edemas size in the tourniquet-compressed limbs, vascular permeability of the skin, general condition and survival rate on a model of post-ischemic toxemia in albino rats it was found that the serum containing antibodies to pancreatic kallikrein (200 gamma/ml), when introduced parenterally (1 ml per 100 g of the mass), increases the survival time of the animals and prevents the development of gangrene in the ischemic limbs. The curative effect of the antikallikrein serum resembles the action of ingitril, a polyvalent inhibitor (1.5 Un. per 100 g of the mass). The antitryptic serum employed in analogous doses stands by its action close to the normal rabbit's serum.